Meningkatkan Kemampuan Motorik Halus Melalui Media Plastisin Pada Anak Tunagrahita Kelas V di SLBN Prof. Dr. Sri Soedewi MS, S.H. Jambi - Desmayati, Helda; Kusumastuti, Grahita (Jurnal Penelitian Pendidikan Khusus, 2024)
This research was based on two visually impaired students who experienced obstacles to fine motor skills so that it affected the learning process and independence. Based on the observation results, students cannot use their fingers properly when clawing small objects and holding pencils. The research method used is classroom action research consisting of two cycles. Each cycle consists of four face-to-face meetings which are carried out in several stages consisting of: planning, implementation of actions, observation and reflection. Three methods of gathering data were used: testing, documentation, and observation. Both quantitative and qualitative methods are used to analyze data. The findings demonstrated that employing plasticine medium to enhance fine motor skills enhanced. Following action, the Supreme Court received a portion of 75%, before being given action of 25% and N got a percentage of 71.8% before being given action of 21.8%%.